KEKATOLIKAN SEKOLAH KATOLIK MENURUT PANDANGAN GEREJA - Herman P. Panda (Program Studi Filsafat Agama Universitas Katolik Widya Mandira Kupang, 2019)
In this article the author presents the views of the Catholic Church herself about the identity of Catholic schools. This view is spread in a number of Church documents both issued by the Vatican II and by the Pope and Roman Dicasteries. According to this view, Catholic schools have a basic call to educate children and young people to become individuals who have integrity, wisdom and firm faith. For this reason, every Catholic School must continue to maintain a supernatural vision, a strong anthropological foundation, an integral education, the spirit of unity and togetherness of all those involved in the educational process and sustained by the living testimony of the teachers.